2000
DOI: 10.1007/s100380050015
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosomal DNA variation in East Asian populations and its potential for inferring the peopling of Korea

Abstract: We have examined variations of five polymorphic loci (DYS287, DXYS5Y, SRY465, DYS19, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 35 publications
(43 reference statements)
6
32
0
Order By: Relevance
“…A summary of the data used in the current study is given in Table 2. The Chinese and Filipino populations are ancestrally related (Melton et al 1995;Kim et al 2000;Miranda et al 2003). Filipinos are a genetic admixture resulting from the migration of various peoples from neighboring countries, including a contribution coming from China (Melton et al 1995;Kim et al 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the data used in the current study is given in Table 2. The Chinese and Filipino populations are ancestrally related (Melton et al 1995;Kim et al 2000;Miranda et al 2003). Filipinos are a genetic admixture resulting from the migration of various peoples from neighboring countries, including a contribution coming from China (Melton et al 1995;Kim et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The Chinese and Filipino populations are ancestrally related (Melton et al 1995;Kim et al 2000;Miranda et al 2003). Filipinos are a genetic admixture resulting from the migration of various peoples from neighboring countries, including a contribution coming from China (Melton et al 1995;Kim et al 2000). These two population groups were targeted for this study primarily because there is a higher rate of CL/P in Asian populations than in European populations (about 1.5/1,000 live births compared to 1/1,000).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to evaluate the association between the guanine-thymine (GT) repeat microsatellite polymorphisms in intron II of the human TLR2 gene, which we previously reported, 32 and the presence of TB in the Korean population, which has reasonable genetic homogeneity. 33 Patients, materials, and methods…”
Section: Introductionmentioning
confidence: 99%
“…Several previous genetic studies among East Asian populations, including a phylogenic study using polymorphic loci on the Y chromosome (Kim et al, 2000) and comparison studies of the distribution of HLA haplotypes (Park et al, 1998), revealed a closer genetic relationship between Japanese and Koreans than relationships between other surveyed Asian populations. These studies showed a higher degree of polymorphism in the distribution of HLA haplotypes among Koreans than in Japanese.…”
Section: Discussionmentioning
confidence: 87%